Development of Indonesian Language Textbooks for Foreign Speakers (BIPA) Based on Banten Culture with the TPACK Approach - Purlilaiceu, Purlilaiceu; Munawaroh, Tatu; Amunziah, Nelly (Universitas Muhammadiyah Malang, 2025)
This research is motivated by the need for Indonesian Language teaching materials for Foreign Speakers (BIPA) that are not only oriented towards linguistic aspects, but also instill local cultural values ​​contextually and utilize learning technology. The purpose of this research is to develop a BIPA textbook based on Banten culture by integrating the TPACK (Technological Pedagogical and Content Knowledge) approach to create interactive, meaningful, and culturally insightful language learning. This research uses a research and development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model and applies a mixed methods approach. Qualitative data were obtained through interviews, observations, and documentation with teachers, learners, and experts in BIPA and Banten culture. In contrast, quantitative data were obtained from expert validation results and product practicality tests. The results show that the developed textbook obtained an average validation score of 3.78 out of 4 (very good category) and a practicality level above 80% of the established indicators. This textbook is considered contextual, easy to use, and able to increase motivation and intercultural understanding of foreign learners. The conclusion of this study confirms that the integration of Banten culture and the TPACK approach is effective in producing BIPA teaching materials that are valid, practical, and relevant to the needs of Indonesian language learning in the digital and global era.